Тенденції розвитку торговельно-економічних відносин в сучасних умовах - Желібо, Євген Петрович; Сагайдак, Юлія Анатоліївна; Харченко, Тетяна Борисівна (Бізнес-навігатор, 2019)
В статті висвітлено сучасний стан розвитку торговельно-економічних відносин України з іншими країнами світу. Проаналізовано основні чинники, що впливають на розвиток торговельно-економічних відносин, зокрема: соціально-економічні, політичні та соціальні чинники, що відображають розвиток вітчизняної зовнішньої торгівлі в розрізі географічної та товарної структури експорту та імпорту. Визначено, що у розвинутих країн експорт, як правило, перевищує імпорт, а в Україні останніми роками спостерігається обернена ситуація. Зроблено висновок, що країни Європейського Союзу є важливими торговельними партнерами держави. Визначено, що основними загрозами ефективного розвитку торговельно-економічних відносин є посилення політики протекціонізму, китайська експансія на світовому ринку, зміна структури ринку зайнятості. Визначено найближчі перспективи розвитку торговельно-економічних відносин України.

The article highlights the current state of development of trade and economic relations of Ukraine with other countries of the world. It is proved that for today, deepening of trade and economic relations of Ukraine, integration of its economy into the European space is a priority task of development. The main factors that have an impact on the development of trade and economic relations are analyzed, in particular: socioeconomic and political, social factors reflecting the development of domestic foreign trade in terms of geographical and commodity structure of exports and imports. It is determined that in developed countries, exports tend to exceed imports, and in recent years Ukraine has seen an inverted situation, which indicates about absence of the majority of goods on the domestic market that are needed to meet the needs of the population, and the development of the Ukrainian economy today is aimed at reducing high-tech industries and orientation on the production of raw materials for export abroad. As a result of the analysis, it is established that the main problems of modern development of Ukrainian exports, which should be concentrated on the Government's efforts are: raw material nature of a large part of exports; the absence of a well-defined policy of structural changes in the material and technical base of industries and technologies of economic sectors; lack of legal basis for introduction of financial mechanisms of state support for export development; insufficient level of investment in modernization of export-oriented industries and a severe lack of new technologies; the dissemination of restrictive and protectionist practices by individual countries and leading transnational corporations; export settlement through offshore companies and tax evasion. It is concluded that the countries of the European Union are important trading partners of the country. It has been determined that the main threats to the effective development of trade and economic relationship are the strengthening policy of protectionist, Chinese expansion in the world market, and changing the structure of the employment market. The short-term prospects of development of trade and economic relations of Ukraine are determined.
Keywords: торгівля; міжнародна торгівля; європейське співробітництво; торговельно-економічні відносини; світова організація торгівлі; глобалізація; trade; international trade; European cooperation; trade and economic relations; world trade organization; globalization